Plaque‐removing efficacy of new and used manual toothbrushes – a professional brushing study. Issue 4 (18th March 2013) - Rosema, NAM; Hennequin‐Hoenderdos, NL; Versteeg, PA; van, WH; van der, U; van der, GA
Abstract Objectives The present study assessed whether 3‐month‐old used manual toothbrushes are less effective in reducing plaque scores compared with new toothbrushes with or without the use of dentifrice. Material and methods The present study was performed employing a single‐use, examiner‐blinded, professional brushing model. Four brushing modalities were randomly allocated to one of four quadrants, that is, 3‐month‐old used toothbrushes and new toothbrushes both with and without the use of dentifrice. Prebrushing and post‐brushing plaque scores (Quigley Hein plaque index) and gingival abrasion (GA) scores were obtained. A dental hygienist performed the professional brushing procedure. The 3‐month‐old used toothbrushes were assessed for wear. Results No significant differences were observed among the treatments with regard to the prebrushing scores. The post‐brushing plaque scores ranged from 1.59 for the new brush with dentifrice to 1.76 for the old brush with dentifrice. There was a significant difference (P = 0.036) among the four treatments regarding the old brush with dentifrice, which removed less plaque than the other treatment modalities. Regarding GA scores, no significant differences were observed. With regard to toothbrush wear after 3 months of use, the scores varied widely among the individually evaluated brushes. Conclusion The present study did not show a clinically relevant difference in plaque score reductions following a 2‐minute brushing exercise among 3‐month‐old used and new manual toothbrushes. However, the wear rate of the brushes seemed to be the determining factor in loss of efficacy, rather than the age of the toothbrush. Furthermore, dentifrice did not show an additional effect on instant plaque removal.